PENGARUH CITRA MEREK DAN IKLAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK - THERESIA PRADIANI; DWI CITRA WAHYU NINGTYAS (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2017)
The purpose of this research is to know the influence of brand image and advertisement on Samsung brand smartphone purchase decision either partially, simultaneously, and dominantly. Data collection was done by distributing questionnaires to 100 respondents by using purposive sampling technique and the respondents in this research are STIE AsiaMalang students. Data were analyzed by multiple linear regression method, Determination Test (R2), Test t, F Test, and Dominant Test. Results of multiple linear regression analysisobtained results the independent variables that have the most influence on the dependent variable are brand image variable with Beta (β) 0,465 value followed by advertisement variable with Beta (β) 0,400. Result of t test to prove the variable of brand image and advertisement have positive and significant influence to decision of Samsung brand smartphone purchase, with t value of each variable of advertisement equal to 5,258 with signification level 0,000 and brand image variable equal to 6,100 with 0.000 significance level. F test results also membutktikan that independent variables of brand image and advertising simultaneously affect the decision of Samsung brand smartphone purchase with the value of F arithmetic amounted to 50.695 with a significance level of 0.000. From the results of this study indicate that the independent variables are able to explain 51.1% of Samsung brand smartphone purchase decisions, while the remaining 48.9% is explained by other independent variables that are not examined.Keywords: Brand Image, Advertisement and Purchase Decision.